2017
DOI: 10.1111/jcpt.12493
|View full text |Cite
|
Sign up to set email alerts
|

The influence of combination use of CYP450 inducers on the pharmacokinetics of voriconazole: a systematic review

Abstract: SUMMARYWhat is known and objectives: Voriconazole is a triazole antifungal agent and is extensively metabolized via cytochrome P450 (CYP450); therefore, special precautions need to be taken when co-administered with a known CYP450 inducer, which may lead to treatment failure. The influence of some CYP450 inducers on the pharmacokinetics of voriconazole has been described in previous studies, but a systematic review was lacking. In this study, we carried out a systematic review to assess the influence of CYP450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 59 publications
0
19
1
Order By: Relevance
“…The effect of glucocorticoids on VRC exposure remains controversial. Some studies have found that they reduced the VRC concentrations, whereas others have made contradictory findings , which may have been due to different types and doses of glucocorticoids. Similarly to our retrospective study , neither PPIs (including lansoprazole and ilaprazole) nor glucocorticoids (methylprednisolone) seemed to affect the VRC pharmacokinetic parameters in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of glucocorticoids on VRC exposure remains controversial. Some studies have found that they reduced the VRC concentrations, whereas others have made contradictory findings , which may have been due to different types and doses of glucocorticoids. Similarly to our retrospective study , neither PPIs (including lansoprazole and ilaprazole) nor glucocorticoids (methylprednisolone) seemed to affect the VRC pharmacokinetic parameters in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Concomitant use of several drugs had a significant impact on VRZ PK. 23 , 24 The quality of evidence varied from high to very low. The CYP2C19 polymorphism was not associated with the rates of treatment response (low quality of evidence), hepatotoxicity (very low quality of evidence), or nervous system/psychiatric disorders (very low quality of evidence).…”
Section: Resultsmentioning
confidence: 99%
“…Summary of the evidence is shown in Refs. 23 and 24 Supplemental Digital Content 1 , http://links.lww.com/TDM/A265 . The concomitant use of CYP450 inducers or inhibitors, especially drugs inducing or inhibiting CYP3A4 or CYP2C19, is very likely to influence VRZ PK and clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The benefit of adding amphotericin B or an echinocandin to voriconazole is uncertain, although in a subset of patients with invasive aspergillosis and an elevated serum GM, those receiving combination therapy with voriconazole and anidulafungin had a lower 6-week mortality relative to patients who received voriconazole alone [17] . We opted to treat our patient with combination therapy because of concern that we would be unable to achieve therapeutic voriconazole levels due to the recent administration of rifampin for presumed bacterial prosthetic valve endocarditis [18] . Indeed, after 1 week of therapy, the patient's serum voriconazole level was subtherapeutic at 1.2 µg/ml.…”
Section: Discussionmentioning
confidence: 99%